As barreiras de ordem linguística na resolução de enunciados de questões escolares: um olhar sobre o processo de produção de sentidos - Melany Maria Baliza Lasmar (2023)
Among plenty of texts and genres that are part of the scholar practice, there is a particular one which is often present in the daily routine of students and teachers: the statements of school exercises. Despite being widely used in education, these didactic texts often receive little attention beyond their function as assessment tools and, therefore, they are overlooked as genres that can be subject to analysis and systematization. Unfortunately, this neglect has resulted in a widespread issue among students that goes beyond the scope of the Portuguese language: difficulties in solving school exercises, often hastily attributed to specific subjects or areas of knowledge. Our hypothesis, however, challenges this notion, suggesting that the main challenge lies not in comprehending the content itself, but in effectively interpreting what is being asked, that is, it consists of a difficulty of textual comprehension. In front this issue, our research aims to explore how factors related to textual comprehension affect students' ability to solve these questions, in order to understand their underlying causes better. Therefore, to achieve this goal, we conducted an in-depth analysis of the “school exercise” genre, utilizing a corpus from the "Sistema Mineiro de Avaliação e Equidade da Educação Pública" (SIMAVE). This analysis has considered the factors that either facilitate or hinder comprehension, based on specific research focused on analysis of school exercises statements and studies about reading and comprehension, as well. The findings revealed that factors such overload of information, textual organization, implicit information demands, lack of lexical knowledge, syntactic complexity and lexical infrequency had significantly impact students' comprehension. Additionally, the type of textual sequence and the necessity to infer implicit information from the statements are crucial aspects affecting students' reading process. These results emphasize the importance of developing inferential skills and information retrieval abilities, as well as the role of lexicon and syntax in constructing meaning. Lastly, we emphasize the need to adopt an integrated approach that encompasses reading, writing, and linguistic analysis in order to fostering contextualized and meaningful teaching